Profil keterampilan transisi mahasiswa: Studi deskriptif kuantitatif pada aspek komunikasi, kolaborasi, dan berpikir kritis-kreatif - Harlis, Harlis; Aswan, Dara Mutiara; Budiarti, Retni S.; Natalia, Desfaur; Johari, Asni (Proceedings Academic Universitas Jambi, 2025)
Higher education is a transitional period from school to the professional world. As a transitional period, higher education plays a role in equipping students with the skills needed to face the challenges of the 21st-century workplace. These skills are also called transition skills. This study aims to describe the profile of students' transition skills, especially in the aspects of communication, collaboration, critical thinking, and creative thinking. This research is a quantitative descriptive study. The subjects of this study were students of the Department of Biology Education, Universitas Jambi, class of 2025, who are currently in their first semester. Data on communication and collaboration skills were collected using a questionnaire instrument using a Likert scale of 1-4, while data on critical and creative thinking skills were collected using an instrument in the form of essay questions that can measure analytical skills and idea elaboration. Data analysis was carried out descriptively by calculating the average value and percentage of achievement for each measured indicator. The results of the study indicate that the transition skills of communication and collaboration aspects are in the moderate category, while the critical and creative thinking skills are still in the low category and require reinforcement through the learning process. The results of this study can be used as a basis for developing programs to improve students' transition skills through learning progress.